The effect of zinc fertilization on yield and quality of commercial processing tomato (Solanum lycopersicum L.) cultivars* - Nas, Yahya; Duman, Ibrahim (Ege Universitesi, 2024)
Objective: In this study, conducted in two production seasons, the effects of zinc fertilization on yield and fruit quality of processing tomato varieties (H-1015, Lalin and Kendras) were investigated. Material and Method: Material consisted of 'H-1015', 'Lalin', and Kendras' processing tomato varieties. The study consisted of 3 different treatments; zinc applied plots, zinc-free plots and control. Results: The results showed that zinc application to H-1015 and Lalin cultivars gave the highest yield values compared to zinc-free and control treatments in both production seasons. While the differences between the pulp colour values L*and a/b were found to be insignificant in both years, the differences between the values of a*and b*were found to be significant in both years. Similarly, zinc fertilization had no positive effects on the TA and lycopene contents of the varieties. The differences between the fruit pH values of the varieties were found to be significant. While the differences among the Brix values were found to be significant only in 2018, the variety H-1015 showed the highest Brix values in both testing years. Conclusion: Zinc fertilization is proposed to obtain a high yield in processing tomatoes. © 2024 Ege Universitesi. All rights reserved.
Keywords: Fruit quality; lycopene; processing tomato; yield; zinc sulfate